Ongoing Neotectonic Activity in the Timiskaming ─ Kipawa Area of Ontario and Québec - Doughty, Michael; Eyles, Nick; Daurio, Louise (Geoscience Canada, 2010)
The Timiskaming Graben lies along the border of Ontario and Québec within the Western Québec Seismic Zone – a conspicuous belt of heightened intracratonic seismic activity in eastern Canada. The graben forms a prominent 50-km wide fault-bounded morphotectonic depression partly filled by Lake Timiskaming (ca. 100 km long and 200 m maximum depth). This lake is a postglacial successor to the much larger glacial Lake Barlow, which drained about 8000 years ago, leaving an extensive clay plain (Little Clay plain). Some 1000 kilometres of high resolution seismic sub-bottom data collected from Lake Timiskaming reveal that both late-glacial Barlow and postglacial Holocene sediments are extensively deformed by neotectonic horst and graben structures. The bathymetry of the lake floor is structurally controlled by faulting; graben basins record enhanced postglacial subsidence between parallel bounding faults, one of which is expressed onshore on the surrounding clay plain as a 20-km long, 10-m high scarp. These structures indicate ongoing neotectonic activity on a scale not recognized elsewhere across intracratonic North America. Seismic reflection data confirm the Timiskaming Graben as an intraplate ‘weak zone’ that may contain a long, late Cenozoic sediment record. A program of deep continental drilling within the Timiskaming Graben and extension of the current program of investigating lake-floor geology across the many lakes of the Western Québec Seismic Zone are now needed. SOMMAIRE Le graben de Témiscamingue est situé le long de la frontière entre le Québec et l’Ontario, au sein de la Zone sismique de l’Ouest du Québec – une zone notable de plus grande activité sismique intracratonique de l’est du Canada. Le graben forme une dépression morphotectonique de 50 km de largeur délimitée par des failles, partiellement remplie par le lac Témiscaminque (environ 100 km de long et une profondeur maximale de 200 m). Ce lac est le successeur postglaciaire du lac Barlow, bien plus grand, qui s’est drainé il y a 8 000 ans environ, exposant une grande plaine alluvionnaire argileuse (plaine de Little Clay). Quelques 1 000 km de données sismiques haute résolution des couches proximales du fond du lac Témiscamingue montrent que tant les sédiments holocènes de la fin du lac glaciaire Barlow que les sédiments postglaciaires sont considérablement déformés par des structures néotectonique de horst et graben. La bathymétrie du plancher du lac est structurellement déterminée par la formation de failles; les bassins de graben ont enregistré un accroissement de la subsidence postglaciaire entre les failles bordières, et l’une d’elle se manifeste par un escarpement exondé de 10 m de hauteur sur 20 km de longueur qui surplombe la plaine alluvionnaire environ-nante. Ces éléments structuraux sont l’indication d’une activité néotectonique persistante, à une échelle qui n’existe nulle part ailleurs dans le craton nord-américain. Les données de sismique réflexion confirme que le graben de Témiscamingue est une zone de « faiblesse » intraplaque qui pourrait renfermer un registre sédimentaire Cénozoïque étendu. Il faut maintenant lancer un programme de sondages continentaux profonds à travers le graben de Témiscamingue et prolonger l’actuel programme d’étude géologique des fonds des lacs de la Zone sismique de l’Ouest du Québec.